2002
DOI: 10.1128/jcm.40.8.2876-2885.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Etest and the Sensititre Colorimetric Methods with the NCCLS Proposed Standard for Antifungal Susceptibility Testing of Aspergillus Species

Abstract: The susceptibilities of 25 clinical isolates of Aspergillus fumigatus, A. flavus, A. terreus, A. nidulans, and A. ustus to itraconazole and amphotericin B were determined by an agar diffusion-dilution method (the Etest method) and a colorimetric broth microdilution method (the Sensititre method); and the results were compared with those obtained by the NCCLS proposed standard M-38P method for antifungal susceptibility testing of filamentous fungi. Various MIC endpoints for the three methods were determined vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
57
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 42 publications
11
57
0
Order By: Relevance
“…and Aspergillus spp. (14,15). It changes from blue to pink as a result of growth (16) and allows for the visual and spectrophotometric determination of MIC values.…”
Section: Discussionmentioning
confidence: 99%
“…and Aspergillus spp. (14,15). It changes from blue to pink as a result of growth (16) and allows for the visual and spectrophotometric determination of MIC values.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Meletiadis et al (11) found that itraconazole MICs generated by Sensititre YeastOne were lower than those generated by the NCCLS method.…”
mentioning
confidence: 90%
“…For itraconazole, Meletiadis et al (11) found that the level of agreement between the methods was greater after 48 h of incubation (84.6%) than that after 24 h of incubation (44.6%). Martín-Mazuelos et al (10) also found the best agreement after 48 h of incubation for this antifungal agent (90.2%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the latter methodology is based on visual MIC reading and requires long incubation periods ranging from 24 h for fast-growing fungi, including Rhizopus species, and up to 72 h for slow-growing fungi, such as Scedosporium species, before results are obtained. More objective methods (32) have been developed based on spectrophotometric readings (6,24), colorimetric assays (20,23,25), glucose consumption (13), glucan synthase inhibition (17), or quantification of fungal products (37), but with these methods, the time required to generate the results was not reduced. Although rapid susceptibility testing methods have been developed based on radiometric (26) and flow cytometric (1) assays generating results within 3 h, their use in routine clinical laboratories may be restricted due to the expensive equipment required (flow cytometer) or to the use of potentially hazardous substances.…”
mentioning
confidence: 99%